Identification of emotional and behavior problems in obese children using Child Behavior Checklist (CBCL) and 17-items Pediatric Symptom Checklist (PSC-17) - Dwi Fachri Harahap; Damayanti Rusli Sjarif; Soedjatmiko Soedjatmiko; Dwi Putro Widodo; Mayke Sugianto Tedjasaputra (Indonesian Pediatric Society, 2010)
Background Obesity can result in emotional and behavior problems in school-age children. Child Behavior Checklist (CBCL) is a standard instrument for evaluating behavior problems, however it is considered not practical. The 17-item Pediatric Symptom Checklist (PSC-17) is a more simple instrument but its diagnostic value has never been evaluated in obese children.Objectives To evaluate the diagnostic value of PSC-17 compared to CBCL as the gold standard.Methods This cross-sectional study was done in May - June 2009. Children aged 6-12 years with obesity were included. Parents filled the CBCL and PSC-17 questionnaires. Sensitivity, specificity, predictive values, and likelihood ratios were calculated for PSC-17.Results Most subjects aged 6-9 years (83%). Boys out numbered girls. Emotional and behavior problems detected by CBCL and PSC-17 were identified in 28% and 22% subjects, respectively. The most common problem was internalization (withdrawal, somatic complaints, anxiety/depression). The PSC-17 had sensitivity and specificity of 69.2% and 95.6% respectively. Positive and negative predictive values were 85.7% and 89%, whereas positive and negative likelihood ratios were 15.7 and 0.32.Conclusions The prevalence of emotional and behavior problems detected using CBCL and PSC-17 in obese children was 28% and 22%, respectively. The PSC-17 has moderate sensitivity to screen emotional and behavior problem in obese children.[Paediatr Indones. 2010;50:42-8].